Fragments of Union - Manning, S. author. aut Link
VIII, 339 p. 5 illus.
Keywords: Fragments of Union , a new approach to comparative literary studies, is about forms of connections: between nations, literatures, individuals, words. It asks how, and why, connections get severed, and about the nature of the pieces that remain. Interdisciplinary readings of writings by Scots and Americans re-draw the literary map of both countries during the Enlightenment and Romantic periods. Political, philosophical, cultural and grammatical dimensions give its analysis sharp relevance to the new conditions presented by devolved government in Britain.